PENINGKATAN DAYA SAING UKM MELALUI STANDARISASI PRODUK, PENGELOLAAN PENGETAHUAN DAN TEKNOLOGI INFORMAS - GL. Hery Prasetya (Jurnal Manajemen, 2016)
The role of SME in developing countries is relatively low, especially for their manufacturing product and competitiveness. Therefore, they get difficulties in increasing their output. The condition will be a challenge for Indonesian small and medium enterprises to improve their competitiveness. The current research is intended to know the effect of product standardization, knowledge management and information technology toward the increasing of competitiveness of metal faundry industry in Ceper – Klaten. Of 109 questionaries distributed, 76 ones are collected. Using regression analysis, it is derived that product standardization and knowledge management positively and significantly affect the competitiveness of SME meanwhile information technology doesn’t affect the competitiveness of SME. Determination coefficient value R square is 89,6% and the rest 10,4% is affected by other variables not discussed.